Biography `inside` biography. Tadeusz Różewicz – Janusz Różewicz - Urbańska, Paulina (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
Tadeusz Różewicz’s biography is interpreted from a particular perspective - through the biography of his older brother Janusz. The analysis is based on literary works and intimate memoirs of both brothers. Their reading shows that Janusz’s life shaped Tadeusz’s biography to a large extent, because the author of the `Trap` had more or less consciously created it in default of non – existing biography of his brother. The conclusion is confirmed by the title thesis of the article on the existence of one of the more original biography `inside` biography casus in Polish culture of XX th cenrury.